Analysis Of Factors Determining Factors Of Financial Performance In Tourism Industry Companies In Indonesia - Listya Devi Junaidi; Ratna Dina Marviana (UNIVED Press, 2025)
Since the Covid-19 pandemic, tourism industry companies have experienced losses to bankruptcy. However, in 2022, after the reopening of entertainment and tourism locations, the financial performance of the tourism industry has begun to improve until now. But not all tourism industry companies feel the same way, in fact they are still experiencing losses until now. This can be seen from the value of the company's financial performance as proxied by ROA which is still below the average company health standard of 5.98%. Therefore, the purpose of this study is to analyze the determining factors that influence the financial performance of the tourism industry, namely lavarege, firm size or capital structure. The number of research populations is 30 companies, then reduced using purposive sampling to 24 companies with a 4-year research period (2020-2023). This study uses panel data linear regression analysis which is tested using Eviews 14 software. Then, the researcher also conducted a bankruptcy risk analysis on each company. The results of the study indicate that leverage and firm size are determining factors for financial performance, while capital structure is not a determining factor for financial performance in tourism sector companies listed on the IDX in 2020-2023. Then, the results of the determination coefficient show that the research variables used (leverage, firm size and capital structure) have an influence of only 32.3%. And based on the results of the bankruptcy risk analysis, 4 companies were found to be in the